Autonomous informed consent in term of completeness of medical information disclosure - Ervin Dyah Ayu Masita Dewi; Siswanto Sastrowijoto; Retna Siwi Padmawati (BKM Public Health and Community Medicine, 2021)
Purpose: Many lawsuits filed by patients to doctors exist because patients don’t receive adequate information concerning their illness which mainly resulted from non-exposure to medical treatment risks. The research was performed to identify the completeness of information disclosure by doctors for informed consent purposes from the perspective of respect for autonomy. Method: The research was conducted by a descriptive qualitative method. Researchers had interviewed five surgeons and five adult patients as subjects with high-risk elective surgical treatment in the hospital as case criteria. Surabaya is the location of the research. Conclusion: By non-exposure of complete medical information to patients, decisions made by patients are not autonomous since they have incomplete understanding, and proper disclosure technique for doctors is required.